Interactions between snow and melt ponds in sea-ice models - Lecomte, Olivier; Fichefet, Thierry; Vancoppenolle, Martin; Massonnet, François; In Proceedings of the International Symposium on Sea Ice in a Changing Environment (2014)
Snow cover on sea ice at the end of the winter persists into the early part of the sea-ice melt season, and the spatial distribution of snow affects surface topography, the distribution of initial melt pond formation and its subsequent evolution, especially on first-year ice (FYI). After the initial formation of melt ponds, the low albedo of the ponds compared with snow or bare ice causes the ponds to preferentially absorb solar radiation and therefore further affects surface ice melt. A physically based melt pond model was coupled to the thermodynamic-dynamic Louvain-la-Neuve Sea-Ice Model (LIM, version 3), which recently includes a representation of snow properties and processes. In the new snow scheme, snow is represented in multiple layers with varying thermo–physical properties, and simple parameterizations for blowing snow and fresh water refreezing into the snow were implemented. Several simulations were performed using the combined snow and melt pond configuration to study the impacts of the processes described above on the Arctic sea-ice melt pond fractions. Preliminary results lead to two expected but uncorroborated model behaviors. In the simulations, blowing snow tends to redistribute the accumulation of snow from relatively young ice to the older-deformed ice or causes losses into leads, thus allowing larger pond fractions on FYI. Refreezing of water in the snow on the other hand curtails the amount of meltwater available to feed melt ponds at their onset of formation, but has limited or no impact on the pond fractions at the middle of the melt season when snow has almost entirely melted away.